The relationship between the process of remembering and the process of self- narration in Horlock`s The Book of Lies and Roth`s Indignation - Al-Harby, Najah Naif (Journal of Humanities & Social Sciences, 2019)
In the Book of Lies by Mary Horlock and Indignation by Philip Roth, the relationship between the process of remembering and the process of self -narration is embodied creatively. As a fellow contemporary writer Julian Barnes points out: ‘Memory is identity....You are what you have done; what you have done is in your memory; what you remember defines who you are; when you forget your life you cease to be, even before your death.’([1]).This paper will examine the profound impact of memory on the two narrators (protagonists as well); Catherine and Marcus, and how they construct identity in their narrations` process. It will shed light on how both narrators allow their past to illuminate their current lives. Recollecting past memories of school, campus life, parents and friends has a great influence on narrating the two stories. Moreover, referring to historical memories of Korean War and German occupation of Guernsey is a significant factor of defining the (self) for Catherine and Marcus.